Language Expression and Cognitive Dissonance of Indonesian Millennials in Delivering Ironical Tweets - Andani, Retno Putri; Indah, Rohmani Nur (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1145, 2020)
This paper investigates the use of language expression and cognitive dissonance in the tweets by Indonesian millennials in delivering ironical responses. It identifies the type of language expressions used by ten young male and female users in Indonesian Twitter. The analysis employed the theory of language expressions proposed by Gibbs (2000) and Festinger's theory on cognitive dissonance (1957). The data were collected from the tweets in February 2019. The results show that the language expressions used by young male and female users were different in delivering the  cronical responses. The male users tend to use jocularity expression while female use sarcasm. On cognitive dissonance, Indonesian millennials prefer disagreement to make an excuse from what they believe in as an effort to make their idea acceptable by others. Further studies are recommended to investigate another type of language expression such as the use of hyperbole in delivering ironical responses in social media.